Molecular Characterization of Adult Tumors Diagnosed as Cerebellar Glioblastomas Identifies Subgroups Associated With Prognosis. (24th January 2023) - Picart, Thiébaud; Poncet, Delphine; Barritault, Marc; Bauchet, Luc; Zouaoui, Sonia; Guyotat, Jacques; Gabut, Mathieu; Fina, Frédéric; Honnorat, Jérôme; Figarella-Branger, Dominique; Pallud, Johan; Ducray, François; et al.
Abstract : Adult tumors diagnosed as cerebellar glioblastoma (cGBM) are rare and their optimal classification remains to be determined. The aim of this study was to identify subgroups of cGBM based on targeted molecular analysis. cGBM diagnosed between 2003 and 2017 were identified from the French Brain Tumor Database and reviewed according to the WHO 2021 classification. The following molecular alterations were studied: IDH1/2, H3F3A, FGFR1, BRAF, TERT promoter mutations, EGFR amplification, MGMT promoter methylation, and alternative lengthening of telomere status. DNA methylation profile was assessed in a subset of cases. Eighty-three cGBM were included and could be classified into 6 mutually exclusive subgroups associated with median age at diagnosis (MA) and prognosis: TERT -mutant and/or EGFR -amplified tumors (n=22, 26.5%, MA=62 y, median overall survival [OS]=4 mo), H3K27M-mutant tumors (n=15, 18.1%, MA=48 y, median OS=8 mo), mitogen-activated protein kinases (MAPK) pathway–activated tumors ( FGFR1, BRAF mutation, or occurring in neurofibromatosis type I patients, n=15, 18.1%, MA=48 y, median OS=57 mo), radiation-associated tumors (n=5, 6%, MA=47 y, median OS=5 mo), IDH-mutant tumors (n=1), and unclassified tumors (n=25, 30.1%, MA=63 y, median OS=17 mo). Most MAPK pathway–activated tumors corresponded to high-grade astrocytomas with piloid features based on DNA methylation profiling. In multivariate analysis, MAPK pathway–activating alterations, ATRX loss of expression, and alternative lengthening of telomere positivity were independently associated with a better outcome and TERT / EGFR alterations with a worse outcome. cGBM display an important intertumoral heterogeneity. Targeted molecular analysis enables to classify the majority of tumors diagnosed as cGBM into mutually exclusive and clinically relevant subgroups. The presence of MAPK pathway alterations is associated with a much better prognosis.